Dynamic Capability Drivers and Performance Outcomes of Strategic Import Planning: The Moderating Role of Organizational Resources and Market Factors - Leonidou, Leonidas C.; Palihawadana, Dayananda; Aykol, Bilge; Nilssen, Frode; Christodoulides, Paul (My University, 2025)
Despite the critical role of strategic planning in the importing firms’ success, research on the subject is both limited and dispersed. Building on the theories of Dynamic Capabilities, Resource-based View, and Industrial Organization, this study conceptualizes and tests the role of dynamic capabilities as drivers and business performance as an outcome of effective strategic import planning, given the contingencies caused by organizational resources and market-related factors. Using data collected from 195 British importers that were analyzed with structural equation modeling, the results revealed that market/source sensing, purchasing expertise, functional orchestration, and managerial proactiveness are important dynamic capabilities conducive to effective strategic import planning, with their impact becoming stronger as there is greater availability of financial and human resources. Effective strategic import planning was also found to have a positive impact on business performance, with this becoming weaker under conditions of heightened competitive intensity and market turbulence. Important theoretical and managerial implications are derived from the study findings.
Keywords: Business Strategy and Leadership; Logistics; Expertise; International Business; International Trade; Market Research and Competitive Intelligence; Strategy Implementation in Organizational Management